2020
DOI: 10.3390/nano10061016
|View full text |Cite
|
Sign up to set email alerts
|

Iron Oxide Nanoparticles as Carriers for DOX and Magnetic Hyperthermia after Intratumoral Application into Breast Cancer in Mice: Impact and Future Perspectives

Abstract: There is still a need for improving the treatment of breast cancer with doxorubicin (DOX). In this paper, we functionalized magnetic nanoparticles (MNPs) with DOX and studied the DOX-induced antitumor effects in breast cancer cells (BT474) in the presence of magnetic hyperthermia (43 °C, 1 h). We show that i) intratumoral application of DOX-functionalized MNPs (at least at a concentration of 9.6 nmol DOX/100 mm3 tumor volume) combined with magnetic hyperthermia favors tumor regression in vivo, and there is evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 54 publications
(86 reference statements)
0
26
0
Order By: Relevance
“…The Langmuir technique was used for the formation of analogs of the biological membrane under laboratory conditions. The conditions similar to the physiological environment were maintained to investigate the hybrid interactions with them [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Langmuir technique was used for the formation of analogs of the biological membrane under laboratory conditions. The conditions similar to the physiological environment were maintained to investigate the hybrid interactions with them [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have reported that local HT using magnetic nanoparticles (MNPs) was effective for cancer treatment. Piehler, S. et al (2020) have reported that local magnetic HT using DOX-functionalized MNPs (43 °C, 1 h) was effective for tumor regression in breast cancer cells (BT474) in vivo [ 20 ]. Thus, local HT combined with chemotherapy may be further developed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The expressions for the Néel and Brownian relaxation times, as well as the effective relation time, are given by [ 7 , 46 , 49 ]: where τ 0 = 10 −9 s is the time constant called the attempt time, η (Pa∙s) is the viscosity of the ferrofluid, and V h (m 3 ) is the hydrodynamic volume of the MNP. The parameter ( Γ ) can be defined as [ 34 , 51 ]: where K denotes the anisotropy constant of a magnetic nanoparticle, and V m (m 3 ) is the volume of its magnetic core, given by the formula: where R is the radius of the magnetic particle. The hydrodynamic volume is a function of the non-magnetic hydrodynamic layer thickness δ (m) of MNPs and can be determined from [ 7 , 46 ]: …”
Section: Mathematical Modelingmentioning
confidence: 99%
“…As this, theoretically, does not depend on the product f × H 2 (A 2 /m 2 /s), it seems to be better for comparing various exposure conditions of tested MF samples. The transformation of EM energy is a complex function of the magnetic field strength, electromagnetic field (EMF) frequency, and the concentration of MNPs [ 51 ]. In this regard, Lanier et al [ 52 ] listed different types of MNPs parameters and investigated the correlation between the properties of MNPs and the SLP and ILP values.…”
Section: Introductionmentioning
confidence: 99%